THE CHARACTERS DEVELOPMENT IN THE FILM ALICE IN WONDERLAND BY LEWIS CARROL AND ITS CONTRIBUTION TO TEACHING DRAMA - Candra Nila Pangestuningtyas; Nur Hidayat; Ririn Ambarini (Wawasan Pendidikan, 2023)
In literature, a drama is the portrayal of fictional or non-fictional events through the performance of written dialog (either prose or poetry). Dramas can be performed on stage, on film, or the radio. Dramas are typically called plays. One of the literary to teach drama from is movie. Movie is one form of popular literary work which is presented visually that contains element of narrative or story. The movie is a medium to educate people and improve understanding of particular subject even though it is only in visual form. By using movie, it also can know a lot of information such as learning character development to teaching drama. A movie is a tool to convey a message depending on the audience because movie show the audience to through the visualization. This research design uses qualitative descriptive. The data sources for this research are taken from a movie is titled Alice in Wonderland. After the researcher has collected all the data, the researcher reduces and selects the movie for analysis, after that; the researcher summarize the research result and draw conclusion for the research result. This study analyzes the characters development in the movie Alice in Wonderland and the contribution to teaching drama. The total characters development found in film Alice in Wonderland are 16. They are obedient, imagine, force, surprised, firm, grumpy, like persuade, liar, impressionable, easy to believe, emotional, like affect, cunning, seducer, kind-heart, and seducer.